Music in the Colombian Caribbean celebrations. 17th and 18th centuries - Aschner Restrepo, Camila (Pontificia Universidad Javeriana, 2014)
This work analyzes the way in which a new social order based on the interchange between different cultures was created during the colonial period. The objective is to study the way in which the processes of syncretism and trans- culturation between indians, colonists and black slaves took place in the context of parties and celebrations -official or clandestine- during the XVII and XVIII centuries in Nueva Granada.